To Love Yourself: Psychological Approach to Predict Healthy Lifestyle Behaviour in Adolescents - K. Hedo, Dian Jayantari Putri; Katmini, Katmini (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Adolescents were susceptible to problems and negativity during the pandemic times. There was an increase in adolescents’ consumption of unhealthy foods by 36%, an increase in body weight by 48%, and a decrease in physical activity and exercise by 43% globally. To function optimally in this situation, adolescents needed to do healthy lifestyle behaviour. Adolescents tended to do this when they could love themselves, which was carried out by applying self-compassion and participating in activities that benefit health. This study was conducted in 2021 and aimed to determine the relationship between self-compassion and adolescent participation in healthy lifestyle behaviour. This study used a cross-sectional design. The population was adolescents in Kediri, aged 15-19. The sample was obtained by cluster sampling, totaling 111 respondents. Independent variables were self-compassion and adolescent participation. The dependent variable was healthy lifestyle behaviour. Data were collected by questionnaires and analyzed by regression. Results showed that variables related to healthy lifestyle behaviour were self-compassion and adolescent participation (p0.001). There was a significant relationship between self-compassion (p=0.02) and participation (p0.001) with healthy lifestyle behaviour. Self-compassion and participation were predictors of healthy lifestyle behaviour, simultaneously and individually. Based on the results, adolescents needed to increase their understanding and practice of self-love in performing healthy lifestyle behaviour.